Rubric for E-portfolio Assessment: Define the Standard Criteria - Handayani, Witri; Rozimela, Yenni; Thahar, Harris Effendi; Sari, Indah (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2024)
An e-portfolio is an e-learning tool that also can be utilized as an assessment tool. As it supports student-centered learning in the process, it has the possibility to gain the students' skills and acquisition of the subject matter which will be very useful for their future careers. This study aims to design a rubric that makes a standard for students' guidance in learning to assess themselves as part of an e-portfolio application in the classroom and to simplify the lecturers' work in assessing the students' assignments. The rubric designed in this study was arranged based on Rico’s theory of four aspects of a rubric to assess e-portfolios. The element criteria of the rubrics are competence development, content acquisition, learning process reflection, and e-portfolio display. Meanwhile, the levels of functioning are advanced, moderate, and poor. It is an analytic rubric without a numbered scoring scale, yet the lecturers are free to set the level of measurement range to the level of functioning. After the rubric was completed, it was validated by two assessment validators and got the criteria of very valid. After being validated, the rubric was ready to be tested in the experimental group which will be discussed further in the other publication.